Sudden Sensorineural Hearing Loss in the Only Hearing Ear: Large Vestibular Aqueduct Syndrome. (27th November 2016) - Bal, Kemal Koray; Ismi, Onur; Bucioglu, Helen; Vayısoğlu, Yusuf; Gorur, Kemal
Abstract : Sudden hearing loss in the only hearing ear cases are rarely published in the English literature; most of the cases are idiopathic. It is an otologic emergency needing urgent treatment. Delayed diagnosis can interfere with patient's social life with interrupting the verbal communication. In this case report we presented a 33-year-old female patient having sudden sensorineural hearing loss in the only hearing ear diagnosed as bilateral large vestibular aqueduct syndrome.